Torakoskopická anatomická resekce v rozsahu lobektomie - Hromádka, P; Cernohorský, S; Baader, M; Fidler, F; Skach, J; Príhodová, L (Rozhledy v chirurgii, 2008)
The authors bring their first experience with a purely endoscopic anatomical lung resection - lobectomy with mediastinal lymphadenectomy. At the department of surgery, Liberec Hospital, we have, so far, done 5 operations using this new technique. Once left superior lobectomy and 4 left inferior lobectomies were carried out. We describe the procedures and surgical tactics in thoracoscopic operations using modern staplers and haemoclips. The aim was to compare the results and benefits of purely endoscopic versus "classical" operations and to dismantle the myth of the extreme finacial intensiveness of this procedure.
Keywords: pneumektomie; nádory plic; Thoracoscopy; Female; Aged; Pneumonectomy; Lung Neoplasms; Humans; ženské pohlaví; torakoskopie; mužské pohlaví; senioři; lidé; Male; lidé středního věku; Middle Aged